Crowdsourcing the Perception of the Bicoronal Scar in Open Cranial Vault Reconstruction. Issue 2 (June 2022) - Roy, Tulsi; Chavez, Julia; Cho, David; Sobota, Rafal; Reid, Russell R.
Purpose: Within open cranial vault reconstruction (CVR) for craniosynostosis, efforts have been directed at minimizing the bicoronal scar, which contributes to increased patient stigmatization and decreased parental satisfaction. To understand these esthetic considerations across multiple centers, we evaluated demographic and clinical determinants of patient scar self-consciousness, parental scar satisfaction, and parental satisfaction with their children's overall medical and surgical care. Methods: A 25-item questionnaire was distributed within an 18 500-member craniosynostosis parental online support group. Parents were asked to grade patient scar self-consciousness, parental scar satisfaction, and parental satisfaction with their children's overall care on a 10-point Likert scale. A t -test and linear regression were performed for binary and continuous variables. Results: Of 838 responses, 516 met inclusion criteria. 32% of patients had visible scar alopecia and 25% of respondents reported their child's hair is deliberately styled to disguise the scar. 2% of patients underwent scar revision. Older age, complications, ongoing symptoms, and increased number of surgeries were negatively associated with parental scar satisfaction, patient self-consciousness, and parental satisfaction with overall management. Ethnicity and hair texture were not associated with patient self-consciousness or parental satisfaction with care. Incision type (zig-zag/wavy compared to straight bicoronal incisions) showed no significant difference in subjective outcomes measures or rates of external stigmatizing behavior between the 2 groups. Conclusions: Bicoronal scarring has complex and multifaceted psychosocial effects. Advanced age, complications, ongoing symptoms, and increased number of surgeries are key determinants of patient and parent satisfaction, though parental esthetic satisfaction may be more sensitive to external stigmatizing behavior. This study calls for a reappraisal of conventional teaching regarding the impact of incision design. While craniofacial morphology, neurological development, and social functioning may be more foundational to overall patient and parent satisfaction, the esthetic value of the bicoronal scar should not be undervalued.